Understanding the Intersection of Waqf and Pesantren Culture: A Study on Local Wisdom - Hendra, Hendra; Yousaf, Esha Momena; Rohaya, Alfi Yasmine (Al Mabhats : Jurnal Penelitian Sosial Agama, 2023)
Waqf, as an integral component of the Islamic philanthropic development model, Waqf plays a crucial role in enhancing educational quality. Its economic potential is further amplified through inter-governmental partnerships. This paper aims to elaborates on the potential of waqf as an economic instrument. Utilizing qualitative literature review methods, this article underscores the economic potential of waqf in addressing a range of pertinent issues. The findings of the study reveal that (1) waqf management aligns with economic capabilities; (2) economic management is in accordance with the practices of Prophet Muhammad and his companions; (3) management models are diversifying as an adaptive response to modern economic theory; (4) Waqf holds potential for economic development. Furthermore, this study's outcomes align with the waqf management concept implemented in several countries, demonstrating its success in managing waqf and providing community benefits, all grounded in Islamic teachings.